The Level of Green Supply Chain Practices Adoption in Sri Lankan Manufacturing Companies - Chamari Pamoshika Jayarathna (International Journal of Supply Chain Management, 2016)
It is been topical to discuss about Green Supply Chain Management due to increasing environmental issues all over the world. Therefore many scholars have been given their attention to do more research on this area based on their own countries. Through this study researcher expects to strength existing body of knowledge regarding green supply chain management based on the Sri Lankan context. Thus this paper attempts to identify the current level of green supply chain practices adoption in Sri Lankan manufacturing companies and gives comparative analysis of green supply chain practices adoption with Chinese and Japanese manufacturing companies. For this study structured questionnaire was used to collect data from the sample of 125 manufacturing companies in Sri Lanka and data were analyzed using descriptive analysis. In order to have general understanding about the level of green supply chain practices adoption, five stages of adoption level was used as a theoretical base. Findings of this study will be more contributed to strengthen the green supply chain management further for managers, relevant authorities and the government of Sri Lanka.Key words: Environmental Issues, Green Supply Chain Management, Green Supply Chain Practices, Level of Adoption, Manufacturing Companies.